Tropical cyclone inner core structure and intensity change - Musgrave, Kate D., author; Schubert, Wayne, advisor; Davis, Christopher, advisor; Johnson, Richard, committee member; Thompson, David, committee member; Kirby, Michael, committee member (Colorado State University. Libraries, 2011)
This dissertation focuses on two projects that examine aspects of the relationship between tropical cyclone (TC) storm-scale dynamics and intensity. TC intensity change is a forecast challenge combining influences from the large-scale environment, the underlying ocean state, and the storm-scale dynamics within the TC. In particular structures and processes involving the TC eye are observed to have an impact on current and future intensity. The first project examines observations of TC eyes from aircraft reconnaissance flown into Atlantic basin TCs over the period 1989-2008. Relationships between TC eye diameter and type and intensity and intensity change are investigated. Consistent with previous studies, eye diameter does not display a direct relationship with intensity. Smaller eye diameters are observed at all intensities, though both the most and least intense TCs with eyes have smaller average eye diameters. Smaller eyes also have the largest variability in intensity change. Larger eyes show smaller ranges for intensity change, and the largest eyes tend to maintain or weaken in intensity. TCs with eyes reported had higher intensification rates and higher probabilities of undergoing rapid intensification. The second project takes a theoretical approach to examining the TC response to the location of the convection within the vortex structure using the balanced vortex model. An annular ring of heating is placed along an idealized axisymmetric vortex. The largest increase in intensity is produced when the heating is placed within the radius of maximum winds. Intensification still occurs at a lessened rate when the heating is contained within the vorticity skirt, and when the heating is outside the vorticity skirt the vortex does not intensify. The strength of the vortex increases in all cases, though less so than the intensity when the heating is within the radius of maximum winds.
Keywords: tropical cyclone